The Delphi-Goal Oriented Evaluation Model to Implementing Teaching Factory in Vocational High School at Bogor Regency - Nurrohmawati, Lisna; Sastrawijaya, Yuliatri; Sandi, Efri (IJBLE Scientific Publications Community Inc., 2023)
Learning with teaching factory has a focus point, namely the application of competency-based learning and production-based learning with link and match between Vocational High Schools and industry. This research is a mixed method research. This study uses the Goal Oriented program evaluation model with Delphi method to obtain the opinion of experts to determine the standard of assessment that will be used to measure the implementation of teaching factory. The Goal Oriented evaluation model is used to measure program achievement based on the objectives of the teaching factory program applied to the Vocational High School level. The research was conducted at vocational high school that hold multimedia expertise competencies in Bogor Regency. The research sample consisted of eleven schools with an average overall result in Bogor Regency was 82.23. Based on these values, it can be concluded that the implementation of the teaching factory in Bogor Regency is well implemented.